Aspects of Islamic radicalization in the Balkans after the fall of communism - Dragnea, Mihai; Fitsanakis, Sifis ca. 20./21. Jh.; Trifunović, Darko 1971-; Nomikos, John M.; Stamevski, Vasko; Cupcea, Adriana 1982- (Lausanne Berlin Bruxelles Chennai New York Oxford Peter Lang, 2023)
This book explores the channels through which Islamic fundamentalism has spread among Muslim populations in the Balkans since the fall of communism. The authors collectively examine political and religious ties between Balkan Muslims and various private organizations and state institutions in Muslim states, with a particular focus on the reception of Salafism and its Saudi version, Wahhabism. In that context, they debate the extent to which war crimes committed by Muslims during the Yugoslav Wars were motivated by Salafism, rather than being a result of domestic ethno-national conflicts. Finally, the book also addresses the ideological climate that has generated volunteers for Islamic State (Daesh) in recent years. Cumulatively these essays emphasize the risks to national security in the Western Balkans represented by the return of Islamic State fighters and the spread of so-called jihadist-Salafism within Muslim communities. The volume is intended to help the reader understand the Balkan states' foreign policy as a response towards the Muslim world in the context of the global war against terrorism. It is the outcome of a research project of the Balkan History Association. "This volume shows that the Muslim communities in the Western Balkans are facing an intense propaganda of a radical Islam and the incitement of hatred and various interreligious divisions, aiming to indoctrinate moderate and tolerant Balkan Muslims. Kosovar youth, for instance, are threatened with a very radical ideology that according to the Kosovar imams trained in different fundamentalist madrassas in the Middle East, 'should influence the creation of a type of the new Muslim believer,' who does not know its historical past, nor its national identity or the values of democracy, but only the 'Islamic' values propagated through Salafism." -Kolë Krasniqi, University "Haxhi Zeka" in Peja, Kosovo "Although Islam has historically been a socio-cultural pillar of the Southeast European societies, the latest turmoil and failed revolutions across the Muslim world have influenced some segments of Muslim communities within the same region. This excellent collective volume is a much-needed contribution to tracing out the inconspicuous phenomena of re-Islamisation and looking at the changes in traditional Muslim identities vis-à-vis interpenetrations of foreign forms of Islam. All chapters show remarkable scholarly achievements and the fruitfulness of providing interdisciplinary perspectives on the development of Balkan Muslims after 1989, thereby shedding new light on the future policy challenges and security issues for the region and the whole European continent." -Francesco Trupia, Nicolaus Copernicus University, Poland
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Islam -- Balkan Peninsula; Islamic fundamentalism -- Balkan Peninsula; Islam; Islam; Religion / Islam / General; Balkanhalbinsel; Southeast Europe; Aufsatzsammlung